2003
DOI: 10.3758/bf03202554
|View full text |Cite
|
Sign up to set email alerts
|

Scaling techniques for modeling directional knowledge

Abstract: A common way for researchers to model or graphically portray spatial knowledge of a large environment is by applying multidimensional scaling (MDS) to a set of pairwise distance estimations. We introduce two MDS-like techniques that incorporate people's knowledge of directions instead of (or in addition to) their knowledge of distances. Maps of a familiar environment derived from these procedures were more accurate and were rated by participants as being more accurate than those derived from nonmetric MDS. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Behavioral studies in humans support the proposition that navigation is based on heading vectors rather than step-by-step movement along a path of identifiable locations (Wang and Spelke, 2002;Waller and Haun, 2003;Muehl and Sholl, 2004;Spiers and Maguire, 2007). For example, Bailenson et al (2000) found that, given a choice between equal-distance routes between two points, subjects reliably chose the route whose initial segment direction was closer to the global vector to the goal.…”
Section: Human Navigationmentioning
confidence: 71%
“…Behavioral studies in humans support the proposition that navigation is based on heading vectors rather than step-by-step movement along a path of identifiable locations (Wang and Spelke, 2002;Waller and Haun, 2003;Muehl and Sholl, 2004;Spiers and Maguire, 2007). For example, Bailenson et al (2000) found that, given a choice between equal-distance routes between two points, subjects reliably chose the route whose initial segment direction was closer to the global vector to the goal.…”
Section: Human Navigationmentioning
confidence: 71%
“…To generate such maps, we used a variant of multidimensional scaling (MDS) that uses interpoint bearing estimates (instead of distance estimates) in order to determine a twodimensional map of the environment that maximally fits each participant's data (see Waller & Haun, 2003). Figure 4 illustrates 95% confidence ellipses for the configurations derived from all the participants in both the pointing and the map placement tasks.…”
Section: Resultsmentioning
confidence: 99%
“…However, MDS relies exclusively on estimations of distances to obtain configural representations of locations and ignores directional information (Waller & Haun, 2003). A technique that considers both distance and directional information is the Procrustes technique (Schönemann & Caroll, 1970).…”
Section: Study 1: Computational Text‐based Spatial Estimates Of CImentioning
confidence: 99%